The ineffable allure of sugar – Hammer cake, That Sugar Film and contradictory pleasures. Issue 1 (7th December 2020) - Supski, Sian; Tanner, Claire; Maher, JaneMaree; Wright, Jan; Lindsay, Jo; Leahy, Deana
Abstract: This article explores the complicated place of sugar in the display of family connectedness and health in a white, middle class Australian family. In the context of heightened anxiety about childhood obesity, we present the Baker family as a case study to explore the pleasures and tensions that sugar consumption produces in families. On their birthdays, each child has a luxurious "Hammer Cake" coated in chocolate studded with sweets; simultaneously the family members have also been influenced by the documentary That Sugar Film and check the sugar contents on packages as they shop. We analyze how these pleasures and pressures are balanced: how anxieties about sugar are negotiated and managed in food practices and in the making of family through rituals of celebration. We argue that the concept of "contradictory pleasures, " where certain foods are seen as "excess, " but mobilized for celebration, offers a nuanced and valuable framework to illuminate simultaneously negative and positive attitudes toward certain foods in family food practices and how families navigate multiple influences on these practices, including popular culture and public health discourses.